2017
DOI: 10.1177/0885328217719854
|View full text |Cite
|
Sign up to set email alerts
|

Development of a membrane of poly (L-co-D,L lactic acid-co-trimethylene carbonate) with aloe vera: An alternative biomaterial designed to improve skin healing

Abstract: The search for new therapies and drugs that act as topical agents to relieve pain and control the infectious processes in burns always attracted interest in clinical trials. As an alternative to synthetic drugs, the use of natural extracts is useful in the development of new strategies and formulations for improving the life quality. The aim of this study was to develop a wound dressing using Poly(L-co-D,L lactic acid-co-TMC) (PLDLA-co-TMC) containing aloe vera (AV). This natural plant extract is known for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It was developed by our research group as a promising material, due capacity of PLDLA to its biological reabsorption abilities and biocompatibility. Previous studies in recent literature related to PLDLA-TMC based-materials in skin tissue regeneration 7,8 and tendon 9 demonstrated that the terpolymer is versatile in a wide range of medical applications, as well as presenting biocompatibility characteristics. Furthermore, the TMC shows flexibility and degradation rates consistent with the applications designed to bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…It was developed by our research group as a promising material, due capacity of PLDLA to its biological reabsorption abilities and biocompatibility. Previous studies in recent literature related to PLDLA-TMC based-materials in skin tissue regeneration 7,8 and tendon 9 demonstrated that the terpolymer is versatile in a wide range of medical applications, as well as presenting biocompatibility characteristics. Furthermore, the TMC shows flexibility and degradation rates consistent with the applications designed to bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ideal concentration used is mandatory to determine how inductive the extract could be, i.e., whether it presents bioactive properties. Recently, it was shown that PLDLA-TMC containing Aloe vera could induce even at higher concentrations a strong increase in cell growth . Since the surface topography and the substances released can influence directly cell adhesion, no washing steps were performed for LCSM live-imaging observations.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that PLDLA-TMC containing Aloe vera could induce even at higher concentrations a strong increase in cell growth. 28 Since the surface topography and the substances released can influence directly cell adhesion, no washing steps were performed for LCSM live-imaging observations. In this way, as observed in Figure 8, the fibroblasts adhered to all PLDLA-TMC containing S.T.R.…”
Section: Concentrations Versus Time (H) As Shown In Figurementioning
confidence: 99%
“…21 Therefore, PLDLA would not cause significant foreign body reaction in the long term. Ignatius and Claes, 27 Esposito et al, 28 and Komatsu et al 29 reported that PLDLA and its composites had good histocompatibility and the potential for tissue engineering and craniomaxillofacial surgery. And SR-PLDLA (DL:L, 70:30) plates and screws have been used as self-reinforced bioabsorbable devices intended for the craniomaxillofacial skeleton or cranioplasties in children.…”
Section: Discussionmentioning
confidence: 99%